PENYULUHAN RUMAH PANGAN MANDIRI DI NAGARI SILANTAI, KECAMATAN SUMPUR KUDUS, KABUPATEN SIJUNJUNG, SUMATERA BARAT - Efrizal Efrizal; Nurmiati Nurmiati; Periadnadi Periadnadi; Ando Fernando (BULETIN ILMIAH NAGARI MEMBANGUN, 2018)
The purpose of this extension activity was to share experiences, the application of science, self-potential extraction and problem solving that occurs in the community, especially in agriculture. The method used is survey and observation, counseling, demonstration plot and direct training in field. Based on the survey and primary data from Nagari Silantai, it can be seen that the Nagari located in Sumpur Kudus District is geographically in the position of 0o26'49 "LS and 100o54'29" BT, with an altitude of sea level around 243 m and rainfall of 300-4.000 mm/year. Judging from the topography, Nagari Silantai has a generally wavy and hilly land surface, with an area of ​​about 12.270 Ha. From the observations in the Nagari Silantai field consisting of 4 Jorong namely Jorong Kinkin, Jorong Koto Tangah, Jorong Koto Ateh and Jorong Ujung Koto. Judging from the data of the poor, Nagari Silantai is still classified as a poor economy community. This can be seen from the community poverty rate of 36.4%. Based on the potential of the area and the condition of the people in the Nagantai Silantai, we were encouraged to conduct independent food house extension activities in Nagari Silantai, Sumpur Kudus District, Sijunjung District, West Sumatra. From the results of this extension activity, it was seen that there was a public welcome and enthusiasm to increase knowledge both at the family level or community members' groups to develop food independence, improve the role and function of the Nagari community institutions and develop family awareness to be willing and motivated and able to use the land in its territory to be a source of food and nutrition.